2020
DOI: 10.1177/1010539520983667
|View full text |Cite
|
Sign up to set email alerts
|

The Malaysian Elders Longitudinal Research (MELoR): Prevalence and Factors Associated With Vision Impairment in an Urban Population in Malaysia

Abstract: Low vision and blindness are major health issues affecting ageing population. This cross-sectional study aims to determine the prevalence of visual impairment (VI) in Petaling Jaya North, Petaling Jaya South, and Lembah Pantai using data from the Malaysian Elders Longitudinal Research. There were 1322 participants aged ≥55 years selected by random sampling from parliamentary electoral rolls. Visual acuity was assessed using the logarithm of the minimum angle of resolution chart at 4 m distance. The overall pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This finding is similar to the report by Reddy et al 10 and the National Eye Survey II. 14 In contrast, the prevalence of blindness is lower than that reported in another study conducted in Kuala Lumpur, 12 which is most probably due to the difference in the categorisation of visual acuity-based blindness. The present study defined blindness in accordance with the WHO definition, which is less than 3/60 vision in the better eye with the best corrected vision.…”
Section: Discussionmentioning
confidence: 78%
“…This finding is similar to the report by Reddy et al 10 and the National Eye Survey II. 14 In contrast, the prevalence of blindness is lower than that reported in another study conducted in Kuala Lumpur, 12 which is most probably due to the difference in the categorisation of visual acuity-based blindness. The present study defined blindness in accordance with the WHO definition, which is less than 3/60 vision in the better eye with the best corrected vision.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, other study conducted among older adults with increased risk of dementia reported older age, history of diabetes, depression and current smoking as negative factors and higher self-reported physical activity and intermediate level of education as enabling factors for multidomain intervention (28). Multimorbidity and higher fat free mass appeared to be associated with participation in Ageless intervention, this indicate that perceived illnesses could have motivated participation as it plays importance in treatment outcomes (35).…”
Section: Discussionmentioning
confidence: 87%
“…On the contrary, it is also possible that older adults with higher physical function are more independent and motivated to maintain their functionality (28). None similar local study, however to compare participation among Malaysian older adults in research, previous longitudinal TUA study among Malaysian older adult observed 34.5% defaulter (34) while in another Malaysia Elders Longitudinal Research (MELoR) study 53.1% met the inclusion criteria but did not agree to participate in study (35). Hence, it is challenging to recruit our older adults probably due to family commitment with spouse and grandchildren.…”
Section: Discussionmentioning
confidence: 93%
“…The impairment of vision is a further significant complaint of older people. Its prevalence in people aged 60 years and older was 13% in Malaysia with an increasing trend in older age (39). In a population ≥50 years, another study found 14.6% with impaired vision only, 11.6% with impaired hearing only and 7.6% with both impaired vision and hearing (40).…”
Section: Discussionmentioning
confidence: 99%